Pengembangan E-Modul Berbasis Multipel Representasi pada Pembelajaran Flipped Classroom Materi Laju Reaksi - Tahta Zilli Arsyka, Azzilani; Sri Wahyuni, Tutik (Jurnal Riset Pendidikan Kimia (JRPK), 2021)
This study aims to develop the e-module of reaction rate topic based on multiple representations with the flipped classroom approach as a student self-study facility and to test the feasibility of the e-module based on its validity and readability responses. This research and development used a 4-D model consisting of 4 stages, namely define, design, develop, and disseminate. However, in this study, the stages carried out only reached the develop stage. The e-module product that has been developed is then validated by three validators consisting of one chemistry education lecturer and two chemistry teachers to test its feasibility in terms of material content and media appearance. Then, e-module was revised according to the suggestions from the validators and tested for its readability based on student responses collected through a questionnaire. The results of the validation data analysis of the developed e-module fulfill the eligibility criteria both in terms of material and media with an average percentage of 91.35% and 91.91%, respectively, in a very good category. Meanwhile, the results of the readability test received a positive responses from students with an average percentage of 82.92% in a good category. Thus, the developed e-module is feasible to be implemented in learning reaction rate topic with the flipped classroom approach. Keywords: e-module, multiple representation,flipped classroom, reaction rate